Decentralized H∞ Control for Uncertain Interconnected Systems of Neutral Type via Dynamic Output Feedback - Heli Hu; Dan Zhao (Abstract and Applied Analysis)
The design of the dynamic output feedback H∞ control for uncertain interconnected systems of neutral type is investigated. In the framework of Lyapunov stability theory, a mathematical technique dealing with the nonlinearity on certain matrix variables is developed to obtain the solvability conditions for the anticipated controller. Based on the corresponding LMIs, the anticipated gains for dynamic output feedback can be achieved by solving some algebraic equations. Also, the norm of the transfer function from the disturbance input to the controlled output is less than the given index. A numerical example and the simulation results are given to show the effectiveness of the proposed method.